2016
DOI: 10.1590/1413-70542016401035215
|View full text |Cite
|
Sign up to set email alerts
|

Color, physicochemical parameters and antioxidant potential of whole grape juices subject to different UV-C radiation doses

Abstract: Knowing that moderate stress such as UV radiation can activate defense mechanisms in plants, the use of UV-C radiation appears as hypothesis of a promising technique that would help to stimulate and enhance beneficial compounds for health, through a clean and healthy technology. In this study, the possible induction of secondary metabolism, the increase in the content of phytochemical compounds and physicochemical changes through the use of UV-C radiation were evaluated on whole grape juices produced with Viti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The phytochemical analysis of the aqueous extract of C. quercifolius revealed the presence of phenols, flavones, flavonols, xanthones, catechins, triterpenoids, and tannins. Studies have shown that flavonoids, when ingested on a regular basis through diet, can help prevent chronic non-communicable diseases due to their antioxidant, anti-inflammatory, anti-hyperglycemic, anticarcinogenic and antiatherogenic effects, as well as antibacterial and antiviral activities ( 28 , 29 ). Triterpenoids are metabolites that also have an antidiabetic potential, which act to increase the release of insulin, modifying glucose metabolism, inhibiting hyperglycemic factors, and inhibiting or stimulating enzyme synthesis ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…The phytochemical analysis of the aqueous extract of C. quercifolius revealed the presence of phenols, flavones, flavonols, xanthones, catechins, triterpenoids, and tannins. Studies have shown that flavonoids, when ingested on a regular basis through diet, can help prevent chronic non-communicable diseases due to their antioxidant, anti-inflammatory, anti-hyperglycemic, anticarcinogenic and antiatherogenic effects, as well as antibacterial and antiviral activities ( 28 , 29 ). Triterpenoids are metabolites that also have an antidiabetic potential, which act to increase the release of insulin, modifying glucose metabolism, inhibiting hyperglycemic factors, and inhibiting or stimulating enzyme synthesis ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…During the last decades, the population is increasingly looking to insert plant products with a high content of vitamins, anthocyanins and phenolic compounds into their usual diet, this interest comes from several studies that report that the consumption of these components can bring health benefits (Corbo et al, 2014;Henrique et al, 2016;Buniowska et al, 2017).…”
Section: Introductionmentioning
confidence: 99%